Political-pedagogical unfoldings of bilingualism for deaf people: reflexions and directing - Sueli Fernandes; Laura Ceretta Moreira (Universidade Federal de Santa Maria (UFSM), 2009)
The article talks about bilingualism for deaf people, it's implications in the educational process, as well as in some of the inclusive linguistic politics unfoldings proposed officially from the end of the decade of 1990 for this segment. The sociocultural and linguistic characteristics of the Brazilian deaf people communities are argued and also the importance of the same ones to be known and socially valued. Some lines of direction and challenges are pointed for the access and remaining of the deaf students in the school educational process. Finally, the text reflects about the bilingual education programs for deaf students, considering that these are complex, specially because it crosses economic ideological, cultural contradictory and heterogeneous interests.